1979
DOI: 10.1002/ijc.2910230611
|View full text |Cite
|
Sign up to set email alerts
|

The effect of long‐term food restriction on tumours in rodents

Abstract: The effect of restricting food intake by approximately 20% was studied in rats and mice. Both species were fed as similar "natural" diet composed chiefly of cereals and bone meal. The duration of the rat study was 24 months, but mice were studied for their whole lifespan of 36 months. In the mice, restriction increased longevity, and in both species the incidence of tumours was reduced and the onset delayed. The effect upon the different types of tumour varied; some types appeared to be unaffected by restricti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
51
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(55 citation statements)
references
References 9 publications
4
51
0
Order By: Relevance
“…From these experiments, it was believed that life extension in these GF animals may be characterized by a infectious disease-free status. Data from the second aspect of our experiment agrees with other studies indicating that appropriate food restriction in rodents can increase mean and maximum life spans [1,2,5,8,10,[12][13][14]16,19,[21][22][23].…”
Section: Disussionsupporting
confidence: 91%
See 1 more Smart Citation
“…From these experiments, it was believed that life extension in these GF animals may be characterized by a infectious disease-free status. Data from the second aspect of our experiment agrees with other studies indicating that appropriate food restriction in rodents can increase mean and maximum life spans [1,2,5,8,10,[12][13][14]16,19,[21][22][23].…”
Section: Disussionsupporting
confidence: 91%
“…McCay et al [8] has reported that restric ling the food intake of rats markedly increased life span. Since then, many repetitions of similarly designed experiments have confirmed this fact [1,2,5,10,13,14,16,19,. It therfore appears that food restriction influences basic mechanisms of the aging process common to these animals.…”
mentioning
confidence: 93%
“…Rather, it is the complex interactions of the environment and diet (total caloric intake) with the SD rat's genome that produces or prevents the polygenic phenotype of diabesity from being expressed. It also appears that feeding modified diets with lowered protein, reduced metabolizable energy content, and increased fiber does not necessarily result in the control of diabesity or improved survival if the diets are provided ad libitum (Tucker, 1979;Iwasaki et al, 1988;Masoro et al, 1989;Keenan et al, 1994aKeenan et al, , 1994bKeenan et al, , 1995aKeenan et al, , 1995bKeenan et al, , 2000aKeenan et al, , 2000bRoe et al, 1995;Yu, 1995;Masoro, 1996;Whitaker et al, 1997;Masoro et al, 1996). Only dietary restriction (DR) of all diets tested in rodents consistently improves survival and delays the onset of the spontaneous development of obesity and the degenerative diseases referred to as "diabesity.…”
Section: Discussionmentioning
confidence: 99%
“…DR delays the time of occurrence of various age-associated diseases, including cancer (22)(23)(24), and is a useful modulator of chemical toxicity. However, its mode of action remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%